Reconsidering Authorship in the Ciceronian Corpus through Computational Authorship Attribution - Vainio, Raija; Välimäki, Reima; Hella, Anni; Kaartinen, Marjo; Immonen, Teemu; Vesanto, Aleksi; Ginter, Filip (Ciceroniana On Line, 2019)
In recent years, methods of computational authorship attribution have offered promising results for the reattribution of classical texts. We use and further develop these methods to verify the authorship of several texts belonging or related to the Ciceronian corpus: Rhetorica ad C. Herennium, De inventione, De optimo genere oratorum, and Commentariolum petitionis. We use two classifiers, Support Vector Machine and Convolutional Neural Network, of which the latter is more accurate except in regard to certain aspects of vocabulary. The most important of our results is that Commentariolum petitionis seems to be authored by Marcus Cicero, not by his brother Quintus. Negli ultimi anni metodi computazionali di attribuzione autoriale hanno offerto risultati promettenti nel definire la paternità dei testi classici. Abbiamo usato e affinato tali metodi al fine di verificare l’autore di alcuni testi che appartengono o afferiscono al corpus ciceroniano, quali la Rhetorica ad C. Herennium, il De inventione, il De optimo genere oratorum, il Commentariolum petitionis. Sono stati adoperati due classificatori, la macchina a vettori di supporto e il Convolutional Neural Network. Quest’ultimo è risultato il metodo più accurato, fatta eccezione per alcuni aspetti di lessico. Tra i risultati conseguiti il più importante riguarda la paternità del Commentariolum petitionis, il cui autore sembra essere stato Marco Tullio Cicerone, anziché suo fratello Quinto.